1999
DOI: 10.1191/095968399667529322
|View full text |Cite
|
Sign up to set email alerts
|

Spring-temperature variations in western Himalaya, India, as reconstructed from tree-rings: AD 1390-1987

Abstract: The Himalayan region plays a very important role in influencing the regional and extra-regional circulation system. Long-term instrumental or proxy climate records for this region are scant, but are essential for a global perspective of climate variability. A 598-year (AD 1390-1987) reconstruction of spring (March-May) temperature has been derived for the first time for the western Himalayan region, India using a well replicated ring-width chronology of Himalayan cedar (Cedrus deodara (D. Don) G. Don). The rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…6). The warm periods 1624-1636, 1650-1668, and 1794-1804 are in good agreement with the March-May temperature reconstruction for the western Himalaya (Yadav et al 1999). The western Calibration period 1954-19801981-20061954-2006Verification period 1981-20061954-1980 The regression equation is in the form of y=a+bx, where y denoted the mean May-June temperature, x equaled the value of the ring-width chronology, a and b are the constants a LOOCV represents leave-one-out cross-validation (Michaelsen 1987) **Stands for the significant level of 0.01 Himalayan record also shows cool conditions identified in our reconstruction during 1440-1454, 1515-1527, and 1922-1937 periods.…”
Section: Comparison With Nearby Temperature Reconstructionssupporting
confidence: 64%
See 1 more Smart Citation
“…6). The warm periods 1624-1636, 1650-1668, and 1794-1804 are in good agreement with the March-May temperature reconstruction for the western Himalaya (Yadav et al 1999). The western Calibration period 1954-19801981-20061954-2006Verification period 1981-20061954-1980 The regression equation is in the form of y=a+bx, where y denoted the mean May-June temperature, x equaled the value of the ring-width chronology, a and b are the constants a LOOCV represents leave-one-out cross-validation (Michaelsen 1987) **Stands for the significant level of 0.01 Himalayan record also shows cool conditions identified in our reconstruction during 1440-1454, 1515-1527, and 1922-1937 periods.…”
Section: Comparison With Nearby Temperature Reconstructionssupporting
confidence: 64%
“…Negative influences of early summer warmth on tree growth were reported for S. przewalskii on the northeastern TP (Gou et al 2008;Liang et al 2010;Liu et al 2006;Shao et al 2010;Sheppard et al 2004;Zhang et al 2003). In the western Himalayas, warm summers also limit the growth of Juniperus polycarpos (Yadav et al 2010), Cedrus deodara (Yadav et al 1997(Yadav et al , 1999Yadav et al 2004) and Abies pindrow (Hughes 1992). In addition, Cai et al (2008) found the limiting effect of May-Jun temperature on tree growth of Pinus tabulaeformis from the southeastern Chinese Loess Plateau.…”
Section: Resultsmentioning
confidence: 99%
“…Borgaonkar et al, 1999;Pant et al, 2000;Cook et al, 2003;Ram and Borgaonkar, 2013) and have been used accordingly for temperature and precipitation reconstruction (e.g. Yadav et al, 1997Yadav et al, , 1999Yadav, 2005, 2014;Ram and Borgaonkar, 2014). A significant negative correlation with May temperature has also been detected for Juniperus tibetica on the semiarid southern Tibetan Plateau (He et al, 2013;, a positive relationship, by contrast, for Larix griffithiana in humid Arunachal Pradesh (Chaudhary and Bhattacharyya, 2000).…”
Section: Tree Physiognomy and Growth Patternsmentioning
confidence: 99%
“…The incidence of severe cold in the 1910s-1920s is confirmed by tree-ring records and ice cores from the Tibetan Plateau (Bräuning 2006, Singh et al 2006, Yao et al 2006. The 1930s-1950s period was a relatively prolonged warm period, which was synchronous with a prolonged warm phase in the Himalayan region (Yadav et al 1999, Cook et al 2003 as well as the source region of the Yangtze River (Liang et al 2008) and the western Sichuan Plateau (Li et al 2010). The most noteworthy feature in the 20th century was a clear trend of increasing cold intensity in the 1960s-1980s.…”
mentioning
confidence: 99%